Extraordinary Partnerships How the Arts and Humanities are Transforming America - Henseler, Christine (Lever Press, 2020)
This inspirative and hopeful collection demonstrates that the arts and humanities are entering a renaissance that stands to change the direction of our communities. Community leaders, artists, educators, scholars, and professionals from many fields show how they are creating responsible transformations through partnership in the arts and humanities. The diverse perspectives that come together in this book teach us how to perceive our lives and our disciplines through a broader context. The contributions exemplify how individuals, groups, and organizations use artistic and humanistic principles to explore new structures and novel ways of interacting to reimagine society. They refresh and reinterpret the ways in which we have traditionally assigned space and value to the arts and humanities.